The Space of Care in Times of Pandemic Emergency - Franco, Maria Giulia (E|C, 2024)
During the most serious phases of the pandemic emergency, a new narrative emerged, drawing parallels with a state of war. This narrative has spread awareness in everyone, that reside in a war situation characterized by an invisible enemy to fight, an unknown virus invading the human body. The focus of my study will be on corporeality, both individual and social, in a space reminiscent of war action, the space dedicated to medical care. This proposal aims to demonstrate changes on how different proxemics caused by somatic limitation, conditions the process of care and thus the interaction between the doctor and the patient. The cases of analysis will be both the reports of experiences of doctors and nurses, who worked during the peak contagion period, and a corpus of photographs distributed online, effective in reporting different ways of magnifying the pandemic battle.